2014
DOI: 10.1364/oe.22.029260
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stability analysis for a self-mixing interferometry system

Abstract: A self-mixing interferometry (SMI) system is a laser diode (LD) with an external cavity formed by a moving external target. The behavior of an SMI system is governed by the injection current J to the LD and the parameters associated with the external cavity mainly including optical feedback factor C , the initial external cavity length ( L0 ) and the light phase (∅0) which is mapped to the movement of the target. In this paper, we investigate the dynamic behavior of an SMI system by using the Lang-Kobayashi mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In stable region, for a stationary target, the laser intensity will be constant after the transient state, whereas in semi-stable and unstable region, relaxation oscillation will be undamped and the laser may enter period-one, quasiperiodic or chaotic oscillation under different feedback strength. The work [21,22] discovers that an OFLD can easily and sometimes inevitably enter the period-one oscillation, e.g. for the case when the feedback level factor C is around 2.5, which is quite commonly reported for the moderate feedback regime in the literature.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In stable region, for a stationary target, the laser intensity will be constant after the transient state, whereas in semi-stable and unstable region, relaxation oscillation will be undamped and the laser may enter period-one, quasiperiodic or chaotic oscillation under different feedback strength. The work [21,22] discovers that an OFLD can easily and sometimes inevitably enter the period-one oscillation, e.g. for the case when the feedback level factor C is around 2.5, which is quite commonly reported for the moderate feedback regime in the literature.…”
Section: Introductionmentioning
confidence: 87%
“…However, many works [18][19][20] have demonstrated that an OFLD system with a stationary external target may be unstable under some certain operation conditions, such as in periodic, quasi-periodic or chaotic oscillation state. We studied OFLD signals with a moving target in different conditions and our recent works [21,22] shows that such sensing system may produce different types of OFLD signals which are classified into three regions defined in [21], i.e. stable, semi-stable and unstable region under different feedback level factors C. C is defined as:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that damped oscillation appears on the discontinuous point of the SMI signal when the SMLD system operates in moderate feedback regime and this kind of damped oscillation corresponds to the external cavity mode, which contains information on the target distance and reflectivity. Additionally, our recent work [17,18] shows another kind of oscillation, i.e. undamped relaxation oscillation (RO), may occur when the SMLD operates in moderate or strong feedback regime.…”
Section: Pd Ldmentioning
confidence: 99%
“…In this A B case, ( ) E t and ( ) N t exhibit complicated oscillations rather than a constant level. Depending on the value of C , a recent work in 43 shows that three operational regions (referred to as stable, semi-stable and unstable which are shown in Fig. 9(a)) can be used to describe the behaviour of an SMI.…”
Section: Smi With the Laser Operating At The Relaxation Oscillationmentioning
confidence: 99%